2011
DOI: 10.22358/jafs/66183/2011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of direct-fed microbials and their combinations with yeast culture on <i>in vitro</i> rumen fermentation characteristics

Abstract: This study was conducted to determine the effects of Bacillus licheniformis (Bl) and Clostridium butyricum (Cb) and their combinations with yeast culture on in vitro rumen fermentation in a twoway factorial design. Treatments included Bl or Cb at levels of 0, 0.5, 1, 5 and 10 mg and their combination with yeast culture at 0, 18, 27, 36 and 60 mg per 200 mg substrate, respectively. Gas production was recorded after 2, 4, 6, 9, 12, 24, 36, 48 and 72 h incubation. In vitro organic matter digestibility (IVOMD) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
(35 reference statements)
1
6
2
Order By: Relevance
“…However, after 24 h incubation, similar gas production was observed between the control and treatment with 10 6 CFU/ml C. saccharobutylicum. Our results were consistent with the results reported by Doto and Liu [45], where addition of a butyrate-producing bacteria, C. butyricum, seemingly had no influence on the rate of gas production at 24 h incubation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, after 24 h incubation, similar gas production was observed between the control and treatment with 10 6 CFU/ml C. saccharobutylicum. Our results were consistent with the results reported by Doto and Liu [45], where addition of a butyrate-producing bacteria, C. butyricum, seemingly had no influence on the rate of gas production at 24 h incubation.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, Kowalski et al [57] demonstrated that supplementation of 2% of microencapsulated sodium butyrate had no effect on NH 3 -N concentration in dairy cows. Other studies also revealed that probiotics comprised of Lactobacillus plantarum, Enterococcus faecium and Clostridium butyricum [57] and C. butyricum alone [45] did not influence NH 3 -N concentration. Microbial crude protein (MCP) is the major source of metabolizable protein for ruminant animals because of its quantity and excellent amino acid profile [58].…”
mentioning
confidence: 94%
“…This was probably due to YEFECAP promoting growth of rumen cellulolytic bacteria and lactate-utilizing bacteria. Yeast may also have stimulated bacterial growth through removal of oxygen that occurs in ruminal fluid and in that way can prevent toxicity to the ruminal anaerobes ( Chaucheyras-Durand et al, 2008 ; Doto and Liu, 2011 ). This will in turn increase polysaccharidase and glycoside-hydrolase activities towards lignified plant tissues, “unlocking” the fiber’s digestible fraction (hemicellulose and cellulose), which will be digested by the cellulolytic microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Yeast can promote the growth of cellulolytic bacteria and lactate-utilizing bacteria. Yeast also stimulates bacterial growth through removal of oxygen that occurs in ruminal fluid and in that way prevents oxygen toxicity to the ruminal anaerobes ( Chaucheyras-Durand et al, 2008 ; Doto and Liu, 2011 ). Jouany (2006) reported that yeast culture could consume oxygen in rumen fluid that enters the rumen by coating with feed particles.…”
Section: Resultsmentioning
confidence: 99%